Toxicity and molluscicidal activity of the essential oil Pimenta dioica against the snail Biomphalaria glabrata - Barros Gomes, Paulo Roberto (2019)
Retraction statement We, the Editor and Editor Committeeof Revista Peruana de Biología (RPB) have retracted the article: “Barros Gomes P.R., Batista Reis J., Pêssoa Fernandes R., Mouchrek Filho V.E., Gouveia de Souza A., Alves Fontenele M. and Caetano da Silva J. 2019. Toxicity and molluscicidal activity of the essential oil Pimenta dioica against the snail Biomphalaria glabrata. Revista Peruana De Biología 26 (1), 101-8. https://doi.org/10.15381/rpb.v26i1.15913.” Corresponding author, Paulo Roberto Barros Gomes (August 12, 2019) requested the retraction of the article, because the information, tables and graphics of the article in RPB had already been published previously in another journal: " Everton G.O., Teles A.M., Mouchrek A.N., & M. Filho V.E. Aplicação do Óleo Essencial de Pimenta Dioica Lindl. As Molluscicide in front of Caramujo Transmissor da Esquistossomose. Revista Processos Químicos 12 (23): 85-94 (https://doi.org/10.19142/rpq.v12i23.433)”. The information included in the RPB and Revista Processos Químicos are parts of the results of the thesis: "Chemical characterization, evaluation of toxicity and molluscicidal activity two oils essenciais da folha of Lindic diode pepper, Citrus limon Linneo e Rizoma of Zingiber officinale Roscoe" (https://repositorio.ufpb.br/jspui/handle/tede/7038 ) (2011-05-11) by Romer Pessôa Fernandes, with advisors Victor Elias Mouchrek Filho and Antonio Gouveia de Souza. Editor Committee of RPB, on October 7 and 14, had meetings and conclude that the article will be retracted for duplicate publication and authorship ethical problems. All the authors were mailing on December. 9, 2019. Revista Peruana de Biologia calls for all readers do not cite this work, and apologises to the authors and to readers for the inconvenience caused.